نظام الضمان الإجتماعي كآلية للحماية الإجتماعية في التشريع الجزائري - • شتحونة, عبد القادر (University of Eloued جامعة الوادي, 2023)
التأمينات الاجتماعية تلعب دوراهامافي حياة المجتمع من الناحية الاقتصادية والاجتماعية، حيث تخصص لها الدول مجموعة من الأنظمة والآليات التي يمكن أن تندرج ضمن صناديق متعددة ومتنوعة، وغالبا ماتكون آليات الحماية الاجتماعية في الدول على شكل صناديق للضمان الاجتماعي تؤمن الأخطار الاجتماعية من بطالة وتقاعد وأمراض، والولادة والوفاة في إطار ووفق ما صدر عن الاتفاقيات الدولية التي تشجع الدول على تطبيق أنظمة للضمان الاجتماعي في تشريعاتها الوطنية وتطوير هذه الأنظمة في نطاق حد أدنى من الحماية الاجتماعية. ولقد عرفت الحماية الاجتماعية في الجزائر منذ الاستقلال تطورا كبيرا تجسد من خلال العديد من التنظيمات والقرارات والإجراءات التي تم اتخاذها والتي تهدف إلى تحقيق شمولية التغطية الاجتماعية لكافة الفئات الناشطة والشرائح الاجتماعية وتحسين مستوياتها المعيشة، لهذا أسس المشرع الجزائري، نظاما للحمايةالاجتماعية يتميز بالتنوع ويستجيب لكل احتياجات فئات المجتمع، فشملت الحماية الاجتماعية مجموعة الآليات والمؤسسات ترتكز على مبدأ التضامن والتكافل والتي تضمن للأفراد الحماية من الأخطار الاجتماعية. ومن أجل الإلمام قدر الإمكان، بمعطيات هذه الآليات والقوانين الخاصة بها من حيث المفاهيمالموضوعية والإجرائية، جاء هذا الموضوع من خلال تناولهللنصوص القانونية المتعلقة بتشريع الضمان الاجتماعي وبالأخص النصوص القانونية التي تحكم تسيير وتنظيم وتمويل هذه المنظومة وما يترتب عليها من الحقوق والالتزامات وللوصول إلى معرفة مدى نجاعة وفعالية الضمان الاجتماعي بالنظر إلى القوانين السارية لحماية المؤمن له و كل من في كفالته.Social insurances play an important role in the life of society in economic and social terms, as countries allocate for them a set of systems and mechanisms that can fall within multiple and diverse funds, and often social protection mechanisms in countries are in the form of social security funds that secure social risks such as unemployment, retirement and diseases , birth and death within the framework and in accordance with what was issued by international agreements that encourage countries to apply social security systems in their national legislation and develop these systems within the scope of a minimum level of social protection. Since independence, social protection in Algeria has known a great development embodied through many organizations, decisions and measures that have been taken, which aim to achieve comprehensive social coverage for all active groups and social strata and improve their standards of living. Society groups, social protection included a set of mechanisms and institutions based on the principle of solidarity and interdependence, which guarantee individuals protection from social dangers, In order to get acquainted as much as possible with the data of these mechanisms and their laws in terms of objective and procedural concepts, this topic came through dealing with the legal texts related to social security legislation, in particular the legal texts that govern the management, organization and financing of this system and the consequent rights and obligations and to get to know the extent Efficiency and effectiveness of social security in view of the laws in force to protect the insured and everyone under his sponsorship.
مذكرة ماستر
Keywords: الضمان الاجتماعي، الحمايةالاجتماعية، التأمينات الإجتماعية.; social security, social protection, social insurance